Chemodiversity of tryptamine-derived alkaloids in six Costa Rican Palicourea species (Rubiaceae–Palicoureeae). (November 2017) - Berger, Andreas; Tanuhadi, Elias; Brecker, Lothar; Schinnerl, Johann; Valant-Vetschera, Karin
Abstract: We report 14 harmala and tryptamine-iridoid alkaloids with various tri-, tetra- and pentacyclic cores from leaves and stem bark of six species of the large and complex neotropical genus Palicourea . Among them is the previously undescribed compound deoxostrictosamide which is related to strictosamide, a key intermediate in camptothecin biosynthesis. In addition, we describe the occurrence of 1, 2, 3, 4-tetrahydronorharman-1-one for the first time within Rubiaceae and ophiorine A and B, two alkaloids with an unusual core bearing a betaine function and a zwitterion as new for the genus. Although the other compounds are already known from other species, their degree of structural diversity highlights the remarkable biosynthetic capabilities of the genus Palicourea . Furthermore, the present paper provides additional support for the hypothesis that tryptamine-iridoid alkaloids represent a distinct chemosystematic feature for the genus Palicourea . Graphical abstract: The previously undescribed alkaloid deoxostrictosamide was isolated from leaves of Palicourea winkleri (Rubiaceae). In total, 14 tryptamine-derived alkaloids were isolated from six species of Palicourea . Their structures were elucidated by NMR and MS techniques. Highlights: We report 14 tryptamine-derived alkaloids from six species of Palicourea . These contain various tri-, tetra- and pentacyclic cores. A previously undescribed alkaloid named deoxostrictosamide is described. Structural diversity and chemosystematic significance of alkaloids are discussed.